Homogenitas Pilihan: Studi Kasus Kolonialisme dan Operasi Koteka 1970 - Aji Dwiatmaja, Ignatius (Sanskara Hukum dan HAM, 2025)
This study examines the cultural and human rights implications of the forced displacement of traditional Papuan attire, *koteka*, through the Indonesian government's “Operasi Koteka” in 1970. Employing a qualitative case study approach and utilizing Georg Simmel’s concept of the "tragedy of culture," this paper argues that the shift from indigenous to Western clothing reflects more than a change in material appearance—it marks a loss of identity, spiritual connection, and cultural autonomy. The *koteka*, traditionally worn by men of several Papuan tribes, is not merely a garment, but a cultural symbol deeply rooted in ritual, social structure, and ecological relationships. The state-led intervention that sought to replace the *koteka* under the guise of modernization and public health constitutes a violation of indigenous cultural rights, as enshrined in Indonesia’s Human Rights Law No. 39 of 1999, Article 6(2). This article contends that such actions represent symbolic violence and a denial of the right to cultural self-determination. It calls for participatory, rights-based development policies, and proposes cultural revitalization and inter-cultural dialogue as essential steps in restoring Papuan dignity, identity, and agency in the postcolonial Indonesian state.